Gas emission of anode polymer coating and its influence on applied - Br magnetically insulated ion diode characteristics; Laser and Particle Beams; Vol. 35, iss. 1 - Lopatin V. S. Valery Stepanovich; Tarakanov V. P. Vladimir Pavlovich; Stepanov A. V. Andrey Vladimirovich; Remnev G. E. Gennady Efimovich; Shamanin V. I. Vitaly Igorevich (2017, 2017)
Title screen